Using the basic reproduction ratio to quantify transmission and identify data gaps for epizootic haemorrhagic disease virus - Simon Gubbins (Royal Society Open Science)
Epizootic haemorrhagic disease virus (EHDV) is an arbovirus transmitted by Culicoides biting midges that has recently emerged in Europe. Here, the basic reproduction ratio (R0) was used to quantify the transmission of EHDV and its dependence on temperature for cattle and deer. Using data from the published literature the parameters needed to calculate R0 were estimated with Bayesian methods to incorporate uncertainty in the calculations. The Sobol method of sensitivity analysis was used to determine the parameters having the greatest influence on R0 and, hence, to identify important data gaps. Depending on the strain, the maximum R0 for EHDV varied from 0.7 to 2.5 in cattle and 1.3 to 4.3 in deer. The maximum R0 occurred at temperatures between 22 and 25°C, while the lowest temperature at which R0 exceeded one was between 16 and 20°C. The sensitivity analysis identified the threshold temperature for virus replication, the probability of transmission from host to vector and the vector- to- host ratio as the most important parameters influencing R0. Furthermore, there are only limited data on EHDV in European deer species and on transmission in wildlife and at the livestock/wildlife interface. These data gaps should be the focus of future research.